2018
DOI: 10.3389/fgene.2018.00412
|View full text |Cite
|
Sign up to set email alerts
|

Network, Transcriptomic and Genomic Features Differentiate Genes Relevant for Drug Response

Abstract: Understanding the mechanisms underlying drug therapeutic action and toxicity is crucial for the prevention and management of drug adverse reactions, and paves the way for a more efficient and rational drug design. The characterization of drug targets, drug metabolism proteins, and proteins associated to side effects according to their expression patterns, their tolerance to genomic variation and their role in cellular networks, is a necessary step in this direction. In this contribution, we hypothesize that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Conversely, proteins that are not part of HDG are characterized by lower degree and their role is associated to their own modules in the network. Similar findings were observed in the previous study ( Piñero et al, 2018 ) for Proteins Associated to Drug Toxicity. This suggests that DARTable genes appear to be coordinators and regulators of biological processes and could connect different modules within the network which would be key characteristics of transcription factors and cell signaling.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, proteins that are not part of HDG are characterized by lower degree and their role is associated to their own modules in the network. Similar findings were observed in the previous study ( Piñero et al, 2018 ) for Proteins Associated to Drug Toxicity. This suggests that DARTable genes appear to be coordinators and regulators of biological processes and could connect different modules within the network which would be key characteristics of transcription factors and cell signaling.…”
Section: Discussionsupporting
confidence: 92%
“…The gene expression pattern in a specific tissue is highly influenced by a number of factors that either in isolation, or in combination, may have large effects on the transcription of genes. With the application of global transcriptional analysis, essential functional mechanisms in e.g., drug response or toxicity, may be revealed (16,21,29). We have previously carried out global transcriptional profiling on paired atrial and ventricular biopsies from five male patients who underwent cardiac surgery (4).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of drug development, PINs have been employed to understand the perturbations elicited by drug treatment in cellular processes, and to characterize drug targets ( Yıldırım et al, 2007 ) and side effects ( Wang et al, 2013 ). Recently, Piñero et al (2018) has shown that within the set of drug targets, those that are related to side effects are more central in the interactome at local, global and meso-scale level. In the current study, we have used interactome data to highlight genes with strong molecular data, such as genes LRBA , which showed over 400 interaction partners in BIANA database, being associated to several diseases and involved in the response to DNA damage ( Matsuoka et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%